Utilizing Pragmatic Theory In Arabic Language Teaching: Enhancing Students’ Communication Skills Effectively - Dimyathi, Muhammad Afifudin; Junaedi, Junaedi (Jurnal Edusci, 2025)
Background. Pragmatic theory emphasizes the importance of context in communication, including both linguistic and non-linguistic aspects. Aims. This study aims to explore the role of pragmatic theory in Arabic language teaching, examine its application in the classroom, and identify the challenges encountered in integrating pragmatic theory into Arabic language teaching. Methods. This study used a qualitative approach using the library research method. Result. The results show that pragmatic theory helps students understand language structures and use them appropriately within social and cultural contexts, making communication more meaningful and natural. Conclusion. Despite challenges such as limited teacher understanding, lack of learning resources, and cultural barriers. Implementation. This approach can be optimized through teacher training, the development of communication-based curricula, and the use of digital learning media